Community Empowerment Based on Islamic Economics to Develop an Autonomous Muslim Village at Baliem Valley of Papua - Tiomy Butsianto Adi; Dafrin Mukhsin (Journal of Islamic Economics Lariba, 2022)
Economic Welfare is a fundamental thing that is needed by humans to be able to live and develop, including by Muslim villagers in Papua. This study aims to analyze Community Empowerment Based on Islamic Economics to Develop an Autonomous Muslim Village at the Baliem Valley of Papua. This study uses qualitative data with a naturalistic approach to natural objects that develop as they are, are not manipulated and research does not affect the dynamics of these objects. The data sought is related to the description of the utilization of village potential in realizing an independent village based on an Islamic economy and the efforts made by several Islamic institutions in the Baliem Valley, Papua. The results of the research show that in order to become an independent village and the people live better, what needs to be done is not only structuring aspects of village governance, but also matters relating to its regional aspects, life arrangements and customs, village potential, readiness of social institutions, village politics and economy.